MENGGAMBAR DAN MEWARNAI MENURUNKAN TINGKAT KECEMASAN ANAK YANG DIRAWAT - Widiyono; Badi’ah, Atik (MEDIA ILMU KESEHATAN, 2012)
Background : Hospitalization is a process due to an arranged or emergency reason where children should stay at hospital, get therapy, and care until they may go home. During the process, children can have traumatic experience and heavy anxiety. The reaction of anxiety due to hospitalization are : crying, fear, agressive, often ask, lost control, confuse, reject to eat and reject on invasive procedure. Execution of nursing treatment to child cannot be quit of giving playing therapy as effort to decrease anxiety, increase co-operative behavior to child and as stimulasi for growth and development of child during experiencing treatment in hospital. One of the recommended interventions is play therapy use drawing and coloring. Objective : The objective of the study was to get illustration influence of play therapy use drawing and coloring to anxiety level for pre school age at Pediatric Ward Ar Rahman in general hospital PKU Muhammadiyah Bantul. Method : The study was a pre experiment using one group pre-post test study design. A total 30 respondents were selected by means of purposive sampling. Data were collected using anxiety observation guidance before and after play therapy and analysed with wilcoxon signed rank test with α=0.05. Results: Results of analysis with wilcoxon signed ranks test is significant level < α=0,05. Indicating that there was significant influence of play therapy use drawing and coloring on anxiety level for pre school age at pediatric ward Ar Rahman in general hospital PKU Muhammadiyah Bantul. Conclution : There was influence of play therapy use drawing and coloring to anxiety level in pre school age at Pediatric Ward Ar Rahman in general hospital PKU Muhammadiyah Bantul. Keywords : Play therapy, anxiety, pre school age